Biological Weapons Testing at Porton Down: The Strategic Effacement of Nonhuman Animals, 1947–1955 - Duxbury, Catherine (Humanimalia, 2023)
This article focuses on the use of nonhuman animals for biological weapons testing by military scientists at Porton Down Defence Science and Technology Laboratory, 1948–1955. After the end of the Second World War and the beginning of the Cold War, the British state and its allies invested in new military technologies which could ensure their superiority in times of conflict. My analysis reveals the partial workings of the Porton Down Laboratory through its historical use of nonhuman animals. I demonstrate that nonhuman animals were simultaneously effaced and made visible during biological warfare experiments. This effacement and visibility was dependent on anthropocentric notions of animal subjection whereby their use in experiments made them “seen” as resources for use, yet paradoxically elicited their nonexistence as subjects. I extend the notion of “strategic ignorance” to develop a novel concept of “strategic effacement” to demonstrate this contradictory relationship which both impacted scientific “objectivity” and contributed to the continued exploitation of animals in the laboratory.